Settlement Rates and Settlement Stages in Compulsory Interest Arbitration - Rose, Joseph; Piczak, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
One of the prevailing concerns about compulsory interest arbitration is its possible effect on genuine collective bargaining. Numerous studies report overall settlement rates (i.e., the proportion of settlements achieved prior to the final impasse procedure) are lower in arbitration systems than in strike-based systems. This study attempts to provide a broader assessment of the effect of compulsory arbitration by calculating settlement rates for different settlement stages. Based on over 28,000 collective agreements negotiated in Ontario between 1982 and 1990, our results show that settlement rates were generally lower under arbitration. At the same time, settlement behaviour varied considerably across arbitration Systems. These differences are associated with specific institutional and organizational aspects in bargaining.